2020
DOI: 10.3389/fmicb.2020.01293
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Ameliorates Influenza A H1N1pdm09 Virus-Induced Acute Lung Injury

Abstract: Influenza remains one of the major epidemic diseases worldwide. Acute lung injury mainly caused by excessive pro-inflammatory host immune responses leads to high mortality rates in severe influenza patients. Galectin-1, an animal lectin ubiquitously expressed in mammalian tissues, is reported to play important roles in viral diseases. Here, we established murine and A549 cell models to explore the potential roles of galectin-1 treatment in H1N1pdm09-induced acute lung injury. We found that galectin-1 protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The role of Gal-1 in progression of some type of viral infections is known. Bao et al showed that in in vivo model, treatment with Gal-1 decreased viral titer and inflammatory cell infiltrations in lungs of mice infected with H1N1pdm09 virus, stimulates production of proinflammatory cytokines and chemokines in serum and bronchoalveolar lavage fluid 24 . During Influenza viral infection, level of Gal-1 was increased in lungs of infected mice, while Gal-1 knock-out mice were more prone to Influenza virus infection compared to wild-type group.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Gal-1 in progression of some type of viral infections is known. Bao et al showed that in in vivo model, treatment with Gal-1 decreased viral titer and inflammatory cell infiltrations in lungs of mice infected with H1N1pdm09 virus, stimulates production of proinflammatory cytokines and chemokines in serum and bronchoalveolar lavage fluid 24 . During Influenza viral infection, level of Gal-1 was increased in lungs of infected mice, while Gal-1 knock-out mice were more prone to Influenza virus infection compared to wild-type group.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly proposed that Gal1 is a soluble protein that functions in the extracellular environment by interacting with glycosylated receptors or intracellularly by controlling signaling pathways through protein-glycan or protein-protein interactions [22]. However, the role of Gal1 on IL-6 production is controversial with studies suggesting Gal1 as an inducer [23][24][25] whereas others suggest that Gal1 decreases IL-6 production [13,[26][27][28]. Our data support this last proposition since even adjusting for disease activity, genetic variants in IL-6 or IL-6R or methotrexate dose, LGALS1 variants associated with higher Gal1 serum levels were associated with lower IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Galectin-1 in progression of some type of virus infections is known. Bao et al showed that in in vivo model, treatment with Galectin-1 decreased viral titer and inflammatory cell infiltrations in lungs of mice infected with H1N1pdm09 virus, stimulates production of proinflammatory cytokines and chemokines in serum and bronchoalveolar lavage fluid 23 . During Influenza virus infection, level of Gal-1 was increased in lungs of infected mice, while Gal-1 knock-out mice were more prone to Influenza virus infection compared to wild-type group.…”
Section: Discussionmentioning
confidence: 99%